2006
DOI: 10.1177/0091270006286434
|View full text |Cite
|
Sign up to set email alerts
|

Altered Methylprednisolone Pharmacodynamics in Healthy Subjects With Histamine N‐Methyltransferase C314T Genetic Polymorphism

Abstract: This study investigated the potential differences in methylprednisolone pharmacodynamics between healthy subjects with different histamine N-methyltransferase (HNMT) C314T genotypes. Six individuals with C/C genotype and 4 with C/T genotype were administered a single intravenous dose of methylprednisolone 0.6 mg/kg ideal body weight in a randomized 2-period manner. Methylprednisolone plasma concentrations were fitted with a 1-compartment model. Cortisol and whole blood histamine suppression were assessed by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Therefore, factors influencing cortisol secretion may have an impact on lymphocyte responsiveness. Hon and coworkers investigated the pharmacodynamics of corticosteroids in healthy subjects with and without histamine N-methyltransferase (HNMT) genetic polymorphism (19). Subjects with C/C genotype were more sensitive to corticosteroid inhibition of cortisol secretion (i.e.…”
Section: Placebo and Hydrocortisonementioning
confidence: 99%
“…Therefore, factors influencing cortisol secretion may have an impact on lymphocyte responsiveness. Hon and coworkers investigated the pharmacodynamics of corticosteroids in healthy subjects with and without histamine N-methyltransferase (HNMT) genetic polymorphism (19). Subjects with C/C genotype were more sensitive to corticosteroid inhibition of cortisol secretion (i.e.…”
Section: Placebo and Hydrocortisonementioning
confidence: 99%
“…Because subjects with HNMT C314T polymorphism tended to be less sensitive to the suppressive effects of methylprednisolone on cortisol secretion and because this subject has a wild-type HNMT genotype, 20 pharmacodynamic parameter values for cortisol suppression were compared only to 3 control subjects who have the same HNMT genotype. Whereas most of the pharmacodynamic parameters were not apparently different, the concentration causing 50% inhibition (IC 50 ) for whole blood histamine suppression was lower for the study participant than that for the control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…20 Ten subjects participated and completed the study. We found that 1 subject had distinctly low methylprednisolone clearance, which approximated a 43% decrease compared to that of other subjects.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…28 There are several reasons for such highly variable responses. Some polymorphisms of the gene encoding the glucocorticoid receptor can diminish or enhance sensitivity to glucocorticoids, 40,41 but these polymorphisms are uncommon and unlikely to explain such wide variations in sensitivity. Most differences in corticosteroid sensitivity between people are related to variations in transcription of the glucocorticoid recep-tor gene and to posttranscriptional and posttranslational modifications.…”
mentioning
confidence: 99%